Analysis of Total Phenolic Content in Jamblang Fruit Seeds (Syzygium cumini): A Systematic Literature Review - Ilham Bintang Pratama; Saputra, Ferdyan Pranata; Deden Sukandar (Eureka Herba Indonesia, 2024)
Jamblang seeds contain various bioactive compounds, one of which is phenolic. Phenolic compounds are known to have strong antioxidant activity, which can help protect the body from free radicals and oxidative stress. Free radicals are unstable molecules that can damage body cells and tissues, thereby contributing to various chronic diseases such as cancer, diabetes, and heart disease. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the analysis of total phenolic content in jamblang fruit seeds (Syzygium cumini). This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. The total phenolic content of jamblang fruit seeds ranges from 100-500 mg/g. The highest total phenolic content was found in jamblang fruit seeds originating from Bogor, namely 476.18 mg/g. Jamblang fruit seeds contain quite high levels of phenolic compounds. The total phenolic content of jamblang fruit seeds can vary depending on the growing location, variety, and extraction method used.